2019
DOI: 10.1063/1.5091579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wall boundary on the scrape-off layer losses of high harmonic fast wave in NSTX and NSTX-U

Abstract: We perform numerical simulations of high harmonic fast waves (HHFWs) in the scrape-off-layer (SOL) of National Spherical Torus Experiment (NSTX)/NSTX-U using a recently developed 2D full wave code. We particularly show that a realistic NSTX SOL boundary can significantly affect HHFW propagation and power losses in the SOL. In NSTX SOL boundaries, HHFW is easily localized near the antenna and propagates less to the SOL, and thus, less power is lost to the SOL. We also show that the lower SOL power losses occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…From figure 12 one can also see a clear interaction between HHFWs and SOL plasma all around the device and for all the three cases. This HHFW-SOL interaction tends to increase for lower magnetic field and one can also observe the cavity modes found in the previous 2D AORSA simulations [25,26] and in [27] using an RF code based on finite element method. To make a better connection with the previous 2D AORSA results, we plot in figure 13 the poloidal cross section of the same cases shown in figure 12.…”
Section: Magnetic Field Scansupporting
confidence: 75%
See 2 more Smart Citations
“…From figure 12 one can also see a clear interaction between HHFWs and SOL plasma all around the device and for all the three cases. This HHFW-SOL interaction tends to increase for lower magnetic field and one can also observe the cavity modes found in the previous 2D AORSA simulations [25,26] and in [27] using an RF code based on finite element method. To make a better connection with the previous 2D AORSA results, we plot in figure 13 the poloidal cross section of the same cases shown in figure 12.…”
Section: Magnetic Field Scansupporting
confidence: 75%
“…Two main additional aspects found from HHFW experiments are (i) large amount of RF power missing from the core [5,16,[20][21][22]35] commonly connected with the presence of the bright plasma spirals extending from the regions in front of the antenna to the top and bottom divertors [5,20]; (ii) low HHFW efficiency mainly in H-mode plasma in the presence of neutral beams. From the HHFW modeling point of view, a series of works [24][25][26][27] have been published with the aim to understand some experimental observations. Most of this works have showed that the SOL density in front of the HHFW antenna plays a critical role and for density larger than the FW cut-off, the wave field propagates in the SOL filling the SOL region rather than penetrating to the plasma core as desired.…”
Section: High Harmonic Fast Wave In Nstx/nstx-umentioning
confidence: 99%
See 1 more Smart Citation
“…Bertelli et al [20][21][22][23] found that a standing fast wave trapped between the antenna and the LCFS (a.k.a. an 'annulus resonance' [24,25]), combined with collisional absorption in the edge plasma, can explain some features of the NSTX edge losses.…”
Section: A Fast Wave Standing Wave Between the Antenna And The Plasmamentioning
confidence: 99%
“…The code computes the wave power, Poynting flux, and wave absorption when waves are launched from a source location and successfully used for the several tokamak machines (e.g., Shiraiwa et al, 2017, Bertelli et al, 2020 One advantage of using the FEM is that the local basis functions can be readily adapted to boundary shapes and background parameters, such as multiple particle densities, magnetic field configuration, and strength, and provides higher resolution in regions where solutions exhibit singular behavior and mode conversion occurs. For such reasons, various magnetic field topologies (i.e., planetary magnetospheres and tokamaks) have been adopted in the FW2D code (Kim et al, 2016(Kim et al, , 2017Kim, Bertelli, Ono et al, 2019).…”
Section: Wave Dispersion Relation In Multi-ion Plasmamentioning
confidence: 99%